The `boy scouts` and `bad boys` of skateboarding: a thematic analysis of the bones brigade - Willing, I.; Green, B.; Pavlidis, A. (Sport in Society: Cultures, Commerce, Media, Politics, 2020)
Skateboarding has emerged from an alternative subculture to an influential action sport, boosted by recent inclusion in the Olympic Games. Central to debates in both academic and practice communities are the tensions between skateboarding as a lifestyle and ethos, and skateboarding as an Olympic discipline. This article presents a thematic analysis of The Bones Brigade documentary which follows the rise of Tony Hawk, a high profile skateboarder, and the team he skated with during an important historical era in skating. All are men, presenting an opportunity to investigate masculinity in the sport. We reveal how these pivotal figures embody flexible and overlapping formations of hyper to alternative masculinity. Importantly, we also highlight forms of emotional connection and expressiveness that can unify all skaters. Such insights promote a deeper understanding into diverse formations of masculinity and various expressions of identities in skateboarding and with insights for other action sports.